The effects of individual nonheritable variation on fitness estimation and coexistence. Issue 16 (1st August 2019) - Gomes, M. Gabriela M.; King, Jessica G.; Nunes, Ana; Colegrave, Nick; Hoffmann, Ary A.
Abstract: Demographic theory and data have emphasized that nonheritable variation in individual frailty enables selection within cohorts, affecting the dynamics of a population while being invisible to its evolution. Here, we include the component of individual variation in longevity or viability which is nonheritable in simple bacterial growth models and explore its ecological and evolutionary impacts. First, we find that this variation produces consistent trends in longevity differences between bacterial genotypes when measured across stress gradients. Given that direct measurements of longevity are inevitably biased due to the presence of this variation and ongoing selection, we propose the use of the trend itself for obtaining more exact inferences of genotypic fitness. Second, we show how species or strain coexistence can be enabled by nonheritable variation in longevity or viability. These general conclusions are likely to extend beyond bacterial systems. Abstract : Here, we include the component of individual variation in longevity or viability which is nonheritable in simple bacterial growth models and explore its ecological and evolutionary impacts. We find that this variation produces consistent trends in longevity differences between bacterial genotypes when measured across stress gradients.